Sudden infant death syndrome due to long QT syndrome: a brief review of the genetic substrate and prevalence - Ioakeimidis, Nikolaos S. (J Biol Res (Thessalon), 2017)
The pathophysiological mechanisms which lead to sudden infant death syndrome (SIDS) are not completely understood. Cardiac channelopathies are a well-established causative factor with long QT syndrome (LQTS) being the most frequent one, accounting for approximately 12% of SIDS cases. The genetic substrate of the above arrhythmogenic syndrome has been thoroughly described but only specific gene mutations or polymorphisms have been identified as SIDS causative. The review will focus on the prevalence of LQTS-induced SIDS or near-SIDS cases and the mutations held responsible. A literature search was performed in PubMed and Scopus electronic databases. Search terms used were: long QT syndrome, channelopathies, QT prolongation, cardiac ion channels. The above-mentioned search terms were always combined with the term: sudden infant death syndrome. Study types considered eligible were: case–control, family pedigree analysis, case reports. The prevalence of LQTS-induced SIDS according to six broad genetic studies ranges from 3.9 to 20.6%, with an average of 12%. Since LQTS can be effectively managed, LQTS-related SIDS cases could be prevented, provided that a screening method is efficient enough to detect all the affected infants.